2018
DOI: 10.3390/ma11101912
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasonication-Assisted Cobalt Hydroxide Composite with Enhanced Electrocatalytic Activity toward Oxygen Evolution Reaction

Abstract: A catalyst toward oxygen evolution reaction (OER) was synthesized by depositing cobalt hydroxide on carbon black. Ultrasonication was applied during precipitation to improve the performance of the catalyst. The ultrasonic-assisted process resulted in the refinement of the cobalt hydroxide particles from 400 nm to 50 nm, and the thorough incorporation of these particles with carbon black substrate. The resulting product exhibited enhanced OER catalytic activity with an onset potential of 1.54 V (vs. reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The impedance results obtained for the examined electrodes in this work were generally in line with those OER impedance studies presented by Si et al [35] and by Lyons, and Brandon [28] on cobalt oxide electrodes, and by Choi et al [36] and by Wu, and He [37] on Mo-based composites. Moreover, Table 3 presents a comparison of the impedance-recorded R ct and j (polarization plot-estimated for η = 0.3 V) parameter values in this work (the charge-transfer resistance was derived through the C dl -approximated surface area of the nickel foam electrodes [23,38,39]) with the results recorded on similar electrodes in References [35][36][37]. It should be noted that the R ct results presented for Ni-Mo based electrodes in Refs.…”
Section: Oer Characterizations Of Ni Foam Co-and Mo-modified Ni Foam ...supporting
confidence: 91%
“…The impedance results obtained for the examined electrodes in this work were generally in line with those OER impedance studies presented by Si et al [35] and by Lyons, and Brandon [28] on cobalt oxide electrodes, and by Choi et al [36] and by Wu, and He [37] on Mo-based composites. Moreover, Table 3 presents a comparison of the impedance-recorded R ct and j (polarization plot-estimated for η = 0.3 V) parameter values in this work (the charge-transfer resistance was derived through the C dl -approximated surface area of the nickel foam electrodes [23,38,39]) with the results recorded on similar electrodes in References [35][36][37]. It should be noted that the R ct results presented for Ni-Mo based electrodes in Refs.…”
Section: Oer Characterizations Of Ni Foam Co-and Mo-modified Ni Foam ...supporting
confidence: 91%
“…The XRD analysis revealed that the surface is covered with a thin layer of Co­(OH) 2 , which was verified by the presence of the mixed phase of Co 3 O 4 and Co­(OH) 2 peaks . The observed diffraction peaks are ascribed to the (002), (220), (400), (511), and (440) planes of the Co 3 O 4 nanorods. , It is suppressing the more active (311) peak of Co 3 O 4 after 5000 cycles with the concomitant formation of a more active (100) peak for Co­(OH) 2 . , In addition, the XPS analysis of the sample further supported the presence of Co­(OH) 2 (Figure S15d,e, ESI ). ,, After the durability test, further deconvoluted Co 2p spectra analysis suggested the change in the electronic state, as evidenced from the change in the Co peak position (Figure S15e, ESI ). , The deconvoluted XPS spectra of Co 3 O 4 after ADT evidenced the presence of three different forms of Co ions. Furthermore, to evaluate the dissolution of Co 3 O 4 during the catalytic performance, the inductively coupled plasma (ICP) analysis (Table S3, ESI ) of post ADT Co 3 O 4 /NEGF was performed.…”
Section: Resultsmentioning
confidence: 70%
“…20,46 It is suppressing the more active (311) peak of Co 3 O 4 after 5000 cycles with the concomitant formation of a more active (100) peak for Co(OH) 2 . 46,47 In addition, the XPS analysis of the sample further supported the presence of Co(OH) 2 (Figure S15d,e, ESI). 43,48,49 After the durability test, further deconvoluted Co 2p spectra analysis suggested the change in the electronic state, as evidenced from the change in the Co peak position (Figure S15e, ESI).…”
Section: Resultsmentioning
confidence: 76%
“…In the literature, various circuits are used for impedance spectra fitting in electro catalytic reactions like the ORR, OER, etc. [48][49][50] In the present study, the impedance spectra were fitted with the help of an equivalent circuit as depicted in the inset of Fig. 4c.…”
Section: Dalton Transactions Papermentioning
confidence: 99%